2011
DOI: 10.1007/s10439-011-0263-z
|View full text |Cite
|
Sign up to set email alerts
|

The Quasi-Linear Viscoelastic Properties of Diabetic and Non-Diabetic Plantar Soft Tissue

Abstract: The purpose of this study was to characterize the viscoelastic behavior of diabetic and nondiabetic plantar soft tissue at six ulcer-prone/load-bearing locations beneath the foot to determine any changes that may play a role in diabetic ulcer formation and subsequent amputation in this predisposed population. Four older diabetic and four control fresh frozen cadaveric feet were each dissected to isolate plantar tissue specimens from the hallux, first, third, and fifth metatarsals, lateral midfoot, and calcaneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 44 publications
1
42
1
Order By: Relevance
“…The results showed that stiffness and energy dissipation increase with loading frequency [39,41]. This was completely in contrast with Bennet and Ker's results, which indicated no changes in energy dissipation and stiffness with different testing frequencies [36].…”
Section: In Vitro Testscontrasting
confidence: 56%
See 4 more Smart Citations
“…The results showed that stiffness and energy dissipation increase with loading frequency [39,41]. This was completely in contrast with Bennet and Ker's results, which indicated no changes in energy dissipation and stiffness with different testing frequencies [36].…”
Section: In Vitro Testscontrasting
confidence: 56%
“…While there was no significant difference in the values of viscoelastic coefficients between diabetic and non-diabetic feet, it was claimed that changes in plantar soft tissue were mainly recognised at the structural level, and not reflected effectively at the material level [38,39].…”
Section: In Vitro Testsmentioning
confidence: 99%
See 3 more Smart Citations